THE INFLUENCE OF SOME GEOMETRIC PARAMETERS OF TWO-LINE CARS ON THEIR AERODYNAMIC CHARACTERISTICS - Бегерський, Дмитро; Левківський, Олександр; Багінський, Олександр; Коваль, Андрій; Ільченко, Андрій (SWorldJournal, 2024)
The article shows that the force of air resistance has a significant effect on the power balance of the car’s movement, and its reduction can be one of the ways to improve its fuel efficiency. An analysis of known studies related to the features of the fo